Transcription factor-dependent regulatory networks of sexual reproduction in Fusarium graminearum - Wonyong Kim; Da-Woon Kim; Zheng Wang; Meng Liu; Jeffrey P. Townsend; Frances Trail (mBio)
ABSTRACT Transcription factors (TFs) involved in sexual reproduction in filamentous fungi have been characterized. However, we have little understanding of how these TFs synergize within regulatory networks resulting in sexual development. We investigated 13 TFs in Fusarium graminearum, whose knockouts exhibited abortive or arrested phenotypes during sexual development to elucidate the transcriptional regulatory cascade underlying the development of the sexual fruiting bodies. A Bayesian network of the TFs was inferred based on transcriptomic data from key stages of sexual development. We evaluated in silico knockout impacts to the networks of the developmental phenotypes among the TFs and guided knockout transcriptomics experiments to properly assess regulatory roles of genes with same developmental phenotypes. Additional transcriptome data were collected for the TF knockouts guided by the stage at which their phenotypes appeared and by the cognate in silico prediction. Global TF networks revealed that TFs within the mating-type locus (MAT genes) trigger a transcriptional cascade involving TFs that affected early stages of sexual development. Notably, PNA1, whose knockout mutants produced exceptionally small protoperithecia, was shown to be an upstream activator for MAT genes and several TFs essential for ascospore production. In addition, knockout mutants of SUB1 produced excessive numbers of protoperithecia, wherein MAT genes and pheromone-related genes exhibited dysregulated expression. We conclude that PNA1 and SUB1 play central and suppressive roles in initiating sexual reproduction, respectively. This comprehensive investigation contributes to our understanding of the transcriptional framework governing the multicellular body plan during sexual reproduction in F. graminearum.IMPORTANCEUnderstanding transcriptional regulation of sexual development is crucial to the elucidation of the complex reproductive biology in Fusarium graminearum. We performed gene knockouts on 13 transcription factors (TFs), demonstrating knockout phenotypes affecting distinct stages of sexual development. Using transcriptomic data across stages of sexual development, we inferred a Bayesian network of these TFs that guided experiments to assess the robustness of gene interactions using a systems biology approach. We discovered that the mating-type locus (MAT genes) initiates a transcriptional cascade, with PNA1 identified as an upstream activator essential for early sexual development and ascospore production. Conversely, SUB1 was found to play a suppressive role, with knockout mutants exhibiting excessive protoperithecia due to abnormally high expression of MAT and pheromone-related genes. These findings highlight the central roles of PNA1 and SUB1 in regulating other gene activity related to sexual reproduction, contributing to a deeper understanding of the mechanisms of the multiple TFs that regulate sexual development.